The adverse consequences of perfect and imperfect self-defense as a cause of justification - López Cantoral, Epifanio (2021)
Self-defense -proper and improper- is a legal institute for the defense of one’s own or third parties’ legal interests, which operates in the face of a current or imminent unlawful aggression, which must meet the requirements outlined in article 20, paragraph 3, of the Criminal Code in force. Also, using the right to self-defense as a justification sometimes results in unforeseeable adverse consequences, such as damage or injury to the legal interests of third parties, for example, death or injury to persons. In this sense, using it implies being careful and responsible in each particular circumstance. For example, it is not the same to exercise self-defense in the presence or absence of the persons involved.